Meeting re Asturian miners' orphans, etc. : inter-departmental correspondence - McDonald, Florence
030-0134-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From F. Mc.Donald Department Secretary's To Mr. Bolton Date 29th June, 1938. SUBJECT. Meeting re Asturian Miners' Orphans, etc. Sir Walter would like you to telephone to Schevenels and ask him whether he could be here to meet this Sub-Committee of the Mineworkers at the T.U.C. Office on Tuesday next, 5th July, at 11 a.m. Sir Walter would like you to impress him with the importance of attending and tell him that the Mineworkers have decided to grant a large sum for the relief of Asturian Miners' Orphans, etc. We are anxious to get this dealt with through the International Solidarity Fund. You will see full particulars in the previous correspondence. By the way, Mr. Elvin will not be present. When you have finished with the letter, we can write to Ebby Edwards. 50,000 I think 292/946/30/134